2019
DOI: 10.1371/journal.pone.0226002
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification and characterization of microsatellite markers in black pepper (Piper nigrum): A valuable resource for boosting genomics applications

Abstract: Black pepper is one of the most valued and widely used spices in the world and dominates multi-billion dollar global spices trade. India is amongst the major producers, consumers and exporters of black pepper. In spite of its commercial and cultural importance, black pepper has received meagre attention in terms of generation of genomic resources. Availability of markers distributed throughout the genome would facilitate and accelerate genetic studies, QTL identification, genetic enhancement and crop improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Pentanucleotides, tetranucleotides, and hexanucleotides were less abundant, together accounting for 25.26% (Figure 2A) in the wolfberry genome. Similar results have been reported for several other plant species (Cheng et al, 2016; Kumari et al, 2019; Liu et al, 2018; Pandey et al, 2013). Previous studies have reported that tetranucleotide, pentanucleotide, and hexanucleotide repeats are the most common repeat in the cucumber (Cavagnaro et al, 2010), peanut (Lu et al, 2019), and Gossypium (Wang et al, 2015) genomes, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Pentanucleotides, tetranucleotides, and hexanucleotides were less abundant, together accounting for 25.26% (Figure 2A) in the wolfberry genome. Similar results have been reported for several other plant species (Cheng et al, 2016; Kumari et al, 2019; Liu et al, 2018; Pandey et al, 2013). Previous studies have reported that tetranucleotide, pentanucleotide, and hexanucleotide repeats are the most common repeat in the cucumber (Cavagnaro et al, 2010), peanut (Lu et al, 2019), and Gossypium (Wang et al, 2015) genomes, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that the nature of the most abundant dinucleotide repeat sequences of differs among plant species. For example, AG/CT is most abundant in tea (Liu et al, 2018), foxtail millet (Pandey et al, 2013), and Chinese spring wheat (Han et al, 2015), whereas AT/TA is most abundant in watermelon (Zhu et al, 2016), black pepper (Kumari et al, 2019), and cucumber (Cavagnaro et al, 2010).…”
Section: Frequency Distribution and Characterization Of Microsatellit...mentioning
confidence: 99%
“…With the emergence of NGS technology, the large-scale development of SSR markers based on genome-wide analysis directly or indirectly promotes the rapid development of marker-assisted breeding. A substantial number of SSR markers have been widely recognized in a variety of plants, including black pepper, pepper, pear, bitter gourd, bread wheat, Camellia sinensis and eggplant, by the analysis of genome-wide sequence data generated ( Cui et al, 2017 ; Liu et al, 2018 ; Portis et al, 2018 ; Xue et al, 2018 ; Kumari et al, 2019 ; Uncu, 2019 ; Ahmed et al, 2020 ). In this study, a large number of SSR primer sets were the first ones to be comprehensively and successfully designed from the whole genome of cabbage, which is specific to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The high mutation rates of SSRs make them highly informative and useful for a wide range of applications such as evolutionary research, population genotyping, and markerassisted breeding. Recent studies have utilized genomewide approaches for the development of SSR markers in plants (Shi et al 2014;Deng et al 2016;Kumari et al 2019). Perhaps the main advantage of this strategy is to produce a large number of SSR markers distributed evenly throughout the genome.…”
Section: Discussionmentioning
confidence: 99%